Comparison of Transfection Agents in Forming Complexes with Ferumoxides, Cell Labeling Efficiency, and Cellular Viability - Ali Syed Arbab; Gene Thomus Yocum; Lindsey Bashaw Wilson; Ashari Parwana; Elaine Kay Jordan; Heather Kalish; Joseph Alan Frank (Molecular Imaging)
By complexing ferumoxides or superparamagnetic iron oxide (SPIO) to transfection agents (TAs), it is possible to magnetically label mammalian cells. There has been no systematic study comparing TAs complexed to SPIO as far as cell labeling efficiency and viability. This study investigates the toxicity and labeling efficiency at various doses of FEs complexed to different TAs in mammalian cells. Different classes of TAs were used, such as polycationic amines, dendrimers, and lipid-based agents. Cellular toxicity was measured using doses of TAs from 1 to 50 μg/mL in incubation media. Iron incorporation efficiency was measured by combining various amounts of FEs and different doses of TAs. Lipofectamine2000 showed toxicity at lowest dose (1 μg/mL), whereas FuGENE6 and low molecular weight poly- L -lysine (PLI.) showed the least toxicity. SPIO labeling efficiency was similar with high-molecular-weight PIX (388.1 kDa) and superfect, whereas FuGENE6 and low-molecular-weight PLL were inefficient in labeling cells. Concentrations of 25 to 50 μg/mL of FEs complexed to TAs in media resulted in sufficient endocytosis of the SPIO into endosomes to detect cells on cellular magnetic resonance imaging.